Implementasi Kebijakan Penggunaan Aplikasi Sistem Informasi Kearsipan Terintegrasi (Srikandi) Sebagai Upaya Mitigasi Arsip Kebencanaan - Aristriya, Dian; Tuswoyo, Tuswoyo (Institut Ilmu Sosial dan Manajemen STIAMI, 2024)
The background of this research departs from the phenomenon of the implementation of the use of the Dynamic Archives General Application (SRIKANDI) which is not optimal because the level of employee knowledge about this application is still low. The purpose of this study is to analyze and describe the low level of employee knowledge of employees towards the SRIKANDI application This research uses a qualitative research approach which is a research process to gain understanding based on methods that investigate a phenomenon that occurs. Participants in this study amounted to 4 people using interviews, observation, documentation and literature studies. The results of research on the implementation of the SRIKANDI Application policy in BNPB in terms of communication, resources, disposition and bureaucratic structure, were concluded to have run quite well despite several obstacles such as communication constraints, internet disconnection or system down, limited resources, resistance to changes from users. But obstacles can be overcome continuously. The author suggests the need to increase the capacity of individuals and organizations in using the SRIKANDI application through structured and continuous training, building collaboration with other institutions that use similar applications to share knowledge, experience, and best practices in disaster archive management and providing constructive feedback to application developers.management and providing constructive feedback to application developers